Letter (copy) : Assistance to Republican Spaniards - Tewson, Vincent
1949-09-30 038-0003-001 Secretary's. VT/EK/38. 30th September, 1949. The Lady Layton, Chairman, National Joint Committee for Spanish Relief, 39, Victoria Street, London, S.W.1. Dear Lady Layton, Assistance to Republican Spaniards. I am sorry to have been so long in following up our correspondence on the above matter. I wanted to contact a number of people, but with my own engagements and their's it has been extremely difficult for me to arrive at a definite conclusion. Finally I think I can say that the General Council would not favour taking on the responsibilities which you suggest, but they would not wish to do anything to interfere with the support which you have had from, I believe, certain Trade Unions. There is in London a Trade Union Group of Spanish Workers in Great Britain. The Secretary and Chairman respectively of this Group are Mr. J. Moreno, 9, Orsett Terrace, W.2. and Mr. C. Garcia, 10, Chepstow Villas, W.11. I think it may be worth while your contacting these people to see if there is any way in which they can assist. There are two Spanish Groups in London. The one I have mentioned above is the one with which we have certain contacts - the other Group is Communist dominated. If matters have not moved too far since you last wrote to me, probably you would try out the above suggestion. 292/946/38/3(I)